2001
DOI: 10.1038/sj.onc.1204782
|View full text |Cite
|
Sign up to set email alerts
|

Nck/Dock: an adapter between cell surface receptors and the actin cytoskeleton

Abstract: In response to extracellular signals, cell surface receptors engage in connections with multiple intracellular signaling pathways, leading to the cellular responses such as survival, migration, proliferation and di erentiation. Thè pY?SH2/SH3?e ector' connection is a frequently used scheme by many cell surface receptors, in which SH2/SH3-containing adapters connect protein tyrosine phosphorylation to a variety of downstream e ector pathways. Following the initial landmark ®nding that Grb2 adapter links the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
169
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 129 publications
(163 reference statements)
5
169
1
1
Order By: Relevance
“…We found that the adapter proteins NCK and Crk bound specifically to the Rac1 C-terminal peptide. Although these adapter proteins have been implicated in cell migration (25,26), a direct association with Rho-like GTPases has not been reported previously. The association of Crk to the C termini of Rac2 or Cdc42 was much less or even absent, compared with the Rac1 peptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the adapter proteins NCK and Crk bound specifically to the Rac1 C-terminal peptide. Although these adapter proteins have been implicated in cell migration (25,26), a direct association with Rho-like GTPases has not been reported previously. The association of Crk to the C termini of Rac2 or Cdc42 was much less or even absent, compared with the Rac1 peptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…specificity in their effects on the actin cytoskeleton and cellular morphology. This signaling specificity has been largely ascribed to differences in the effector loop (amino acids [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and the insert region (amino acids 124 -136), domains that are divergent among the different family members. However, the most variable region within the closely related Rho-like GTPases is the C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, under resting conditions, PAK1 to -3 interact with the Nck adapter that upon activation links tyrosine kinase receptors and brings PAK to the membrane (for a review, see Ref. 22). However, PAKs also form stable complexes with the guanine exchange factors for Rac and Cdc42 of the PIX/Cool family, and these interactions are not only closely involved in targeting PAK to the membrane but also in regulating its kinase activity (23)(24)(25).…”
mentioning
confidence: 99%
“…The ETA Receptor Induces the Inhibition of Cell Migration through Nck1 but Not through Grb2 or CrkII-A growing number of studies have suggested that adaptor proteins play an important role in mediating the signaling pathway from receptor tyrosine kinases to the Rho family-dependent regulation of the actin cytoskeleton (25,26). Cell migration is a complex cellular process that is regulated by a number of regulatory proteins and is driven by cytoskeletal reorganization.…”
Section: Resultsmentioning
confidence: 99%